Applying SWAT to predict ortho-phosphate loads and trophic status in four reservoirs in the upper Olifants catchment, South Africa - J. M. Dabrowski (Hydrology and Earth System Sciences, 2014)
Excessive phosphate loading in the upper Olifants River, South Africa has resulted in widespread eutrophication and associated ecosystem health impacts. The majority of sewage treatment works (STWs) are operating poorly and are likely an important source of bioavailable ortho-phosphate (OP) in the catchment. The Soil Water Assessment Tool (SWAT) was used to identify important sources of OP loading in the catchment and to predict changes in the trophic status of four reservoirs associated with three STW effluent OP standards (the current average of 4 mg L−1 and standards of 1 and 0.1 mg L−1). Nash–Sutcliffe and PBIAS statistics showed good model performance for simulations of flow and OP loading using a multi-site calibration and validation approach. Key sub-catchments responsible for high OP loading were identified. Three of the four reservoirs are heavily impacted by OP loading originating from STWs. Two reservoirs show mean annual OP concentrations indicative of eutrophic conditions and a 1 mg L−1 effluent standard would reduce concentrations to well within the mesotrophic range. There was little difference in OP loads and concentrations associated with the 1 and 0.1 mg L−1 effluent standards, indicating that attention to nonpoint sources would be required to realise any benefit associated with the strictest effluent standard. Regression analyses and associated 95% prediction limits between simulated OP loads and concentrations for all effluent treatment scenarios from 2002 to 2010 allowed for the quantification of OP loading that would ensure a specific trophic status in each reservoir. This study is one of the first to apply SWAT in simulating OP loading and concentrations in large reservoirs, and its application in South Africa provides further support for its utility throughout a wide geographical area.